Dark Melody. Book 12 - Feehan, Christine (New York : Avon, 2010)
Searching for the woman he is destined to spend his life with, Dayan, the lead guitarist of the Dark Troubadors and a powerful Carpathian, finds his soulmate in the form of Corinne Wentworth, a beautiful mortal running from her past.
Keywords: Vampires -- Fiction